Continuous Valorization of Glycerol into Solketal: Recent Advances on Catalysts, Processes, and Industrial Perspectives - Isabella Corrêa; Rui P. V. Faria; Alírio E. Rodrigues (Sustainable Chemistry, 2021)
With the global biodiesel production growing as never seen before, encouraged by government policies, fiscal incentives, and emissions laws to control air pollution, there has been the collateral effect of generating massive amounts of crude glycerol, a by-product from the biodiesel industry. The positive effect of minimizing CO2 emissions using biofuels is jeopardized by the fact that the waste generated by this industry represents an enormous environmental disadvantage. The strategy of viewing “waste as a resource” led the scientific community to propose numerous processes that use glycerol as raw material. Solketal, the product of the reaction of glycerol and acetone, stands out as a promising fuel additive capable of enhancing fuel octane number and oxidation stability, diminishing particle emissions and gum formation, and enhancing properties at low temperatures. The production of this chemical can rely on several of the Green Chemistry principles, besides fitting the Circular Economy Model, once it can be reinserted in the biofuel production chain. This paper reviews the recent advances in solketal production, focusing on continuous production processes and on Process Intensification strategies. The performance of different catalysts under various operational conditions is summarized and the proposed industrial solketal production processes are compared.